studying the effect of Rhodamine b concentration on the spectral properties (Journal of the College of Basic Education, 2023)
The effect of the molar concentration of Rhodamine B dye on optical absorption spectra and fluorescence spectra. The results show that the Absorption intensity increased and the fluorescence peaks are blue shifted as the dye molar concentration increased from 1 to 100 M. In addition, the results reveal an enhancement of the absorbance and ﬂuorescence intensity quenching is observed. The obtained ﬂuorescence quenching of the dye higher than 60µM has come from the collisional mechanism. The Beer-Lambert law governs absorbance at low concentrations. While the absorbance deviates from the Beer-Lambert law at high concentrations due to contributions from dimers and dye aggregation.